2018
DOI: 10.1038/s41593-018-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Synaptic N6-methyladenosine (m6A) epitranscriptome reveals functional partitioning of localized transcripts

Abstract: In the version of this article initially published, a Supplementary Fig. 6f was cited in the last paragraph of the Results. No such panel exists; the citation has been deleted. The error has been corrected in the HTML and PDF versions of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several studies have shown that YTHDF1 is a methyl-binding enzyme that mediates the Wnt/ β -catenin signaling pathway and may be an important pathway for its involvement in neurodevelopment and neurological diseases. In addition, it has been shown that m6A affects synaptic plasticity [ 40 ]. m6A promotes learning and memory through its binding protein YTHDF1 in the adult mouse hippocampus in response to neuronal stimulation and facilitates protein translation of target transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that YTHDF1 is a methyl-binding enzyme that mediates the Wnt/ β -catenin signaling pathway and may be an important pathway for its involvement in neurodevelopment and neurological diseases. In addition, it has been shown that m6A affects synaptic plasticity [ 40 ]. m6A promotes learning and memory through its binding protein YTHDF1 in the adult mouse hippocampus in response to neuronal stimulation and facilitates protein translation of target transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…YTHDF3 can specifically recognise m 6 A-modified Apc gene mRNA in the cytoplasm and regulate the translation process with YTHDF1. Deleting YTHDF1 and YTHDF3 can cause abnormal translation of Apc protein, which can induce ectopic neuronal development and attenuate synaptic transmission ability [ 144 ]. YTHDC1 plays a role in premRNA splicing and mediates the nuclear and cytoplasmic transport of methylated mRNAs, thus facilitating neuronal survival and reducing ischaemic stroke by destroying PTEN mRNA and promoting Akt phosphorylation [ 127 ].…”
Section: M 6 a Rna Modification And Bgamentioning
confidence: 99%
“…Recently, the Jaffery lab identified a facilitating role of methylation of adenosine at the nitrogen-6 position (m6A) in LLPS in vitro, and linked the high abundance of m6A RNA to LLPS of specific membraneless organelles (Ries et al, 2019). Interestingly, transcripts critical for synaptic organization and function are highly modified with m6A and are translocated to synapse (Merkurjev et al, 2018). Like the disrupted neuromorphology seen with FMRP mutations (Nimchinsky et al, 2001;Tsang et al, 2019), reducing the levels of the protein "m6A reader", a protein that interacts with m6A-modified mRNA, caused structural and functional deficits in hippocampal dendritic spines (Merkurjev et al, 2018).…”
Section: Llps and Local Protein Synthesismentioning
confidence: 99%
“…Interestingly, transcripts critical for synaptic organization and function are highly modified with m6A and are translocated to synapse (Merkurjev et al, 2018). Like the disrupted neuromorphology seen with FMRP mutations (Nimchinsky et al, 2001;Tsang et al, 2019), reducing the levels of the protein "m6A reader", a protein that interacts with m6A-modified mRNA, caused structural and functional deficits in hippocampal dendritic spines (Merkurjev et al, 2018).…”
Section: Llps and Local Protein Synthesismentioning
confidence: 99%